Thai dominance: UUM All Stars dominate international takraw tourney in Kedah - Noh, Dasheer (The Star, 2011)
UNIVERSITI Utara Malaysia (UUM) All Stars trio smashed their way to the inaugural International Inter-Regu Sepak Takraw title at the Sultan Abdul Halim Stadium in Alor Setar.